Are Congenital Arteriovenous Malformations of Proximal Upper Extremity, More on the Right: Case Report and Literature Review - Parida, Satyen; Gupta, Sumanlata; Chandran, B. V. Sai (International Journal of Angiology, 2016)
This is a case of a 9-year-old boy with a congenital arteriovenous malformation (AVM) of the right upper extremity arising from the right subclavian artery. He underwent open surgical excision of the vascular tumor. Upon reviewing the literature, a high incidence of right-sided congenital AVM of the proximal upper extremity was identified. It has been suggested that this high incidence may be related to the complexity of the embryologic development of the right subclavian artery.
Keywords: AV malformation; subclavian; artery; excision; endovascular technique; arteriovenous fistula